Dynamic simulation of electric machinery : using Matlab/Simulink / [cakera padat] - 209161 Ong, Chee-Mun (Upper Saddle River, N.J. : Prentice Hall, 1998)
System requirements: Windows, Unix or MacOS operating systems; MATLAB and SIMULINK for the relevant operating systems.